Pengaruh Pengalaman Dan Keterikatan Emosional Pada Merk Terhadap Loyalitas Konsumen - Badri Munir Sukoco; Reza Aditya Hartawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
Having consumers who repeatedly purchase the brand is marketers’ desire. This study develops arguments that repeated purchase determined by the experience of customers with the brand as well as how strong their emotional attachment toward the brand. This study further argues that the effects of consumers’ brand experience and emotional attachment to brand are stronger when they are highly involved with the products. Onehundred eighty respondents participated in this study on 6 different famous brands. The results reveal that the effect of brand experience on repurchase intention is mediated by emotional attachment to brand. When consumers highly involve to the product, the effect of brand experience on repurchase intention becomes stronger. Managerial and academic implications are also presented.